The Vatican Council II in the Diary of Otto Semmelroth - Madrigal, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This study presents the history of Vatican II (1962-1965) folowing the pages of the diary of Otto Semmelroth, german Jesuit and expert (peritus) at the Council, an unpublished text, with great interest for the knowledge of some documents as Lumen gentium, Dei Verbum, Gaudium et spes.